Legacies and afterlives of Dutch colonialism: told and imagined accounts of South African colonial histories in contemporary exhibition practice - Valley, Greer (Michaelis School of Fine Art, 2026)
This research takes a critical stance to what is commonly referred to as the ‘decolonial turn' in European museums, exemplified by the recent prevalence of ‘decolonial exhibitions' and programming to be found across the continent. Specifically, it analyses current representations of Dutch colonialism in the Netherlands and South Africa through the case study exhibition: Goede Hoop: South Africa and the Netherlands from 1600, which was on display at the Rijksmuseum in Amsterdam from February 17 to May 21, 2017. Through a close reading of this case, this study examines how questions of national identity, racialised self–and–other ideologies, and notions of epistemic violence and cognitive injustice relate to the materialities of museum display and exhibition practices. By investigating the colonial epistemologies and practices that continue to haunt contemporary European museum exhibitions in the wake of global imperialism, the study evaluates whether exhibitions might serve as interventionist instruments to demolish colonial systems inside museum institutions and build strategies to unlearn imperial knowledge. By analysing the contemporary cultural phenomenon of the ‘decolonial exhibition', the study demonstrates how the practices and approaches adopted in these projects can contradict their stated objectives and fail to address the core challenges and legacies of colonialism. Positioned as benevolent gestures, postcolonial museum exhibitions in the Netherlands and elsewhere in Europe frequently elicit contentious public debates but do little to address the repatriation and restitution of stolen heritage from former colonies and the ongoing, urgent issue of reparations for colonial violence. They instead foster or strengthen colonial assumptions of cultural and racial superiority.